ESTIMATION OF PROBABLE MAXIMUM PRECIPITATION (PMP) AND PROBABLE MAXIMUM FLOOD (PMF) USING GSSHA MODEL (Case Study Area Upper Citarum Watershed) - ROSITA ANGGRAINI SIBUEA - NIM: 12814021, PUJI
Probable Maximum Flood (PMF) used in the design of hydrological structures reliability and safety which its value can obtained from the Probable Maximum Precipitation (PMP). PMP is the theoretical maximum precipitation for a given duration and a particular area. The objectives of this research are estimate PMP and PMF value in Upper Citarum Watershed and know the impact from different PMP value to PMF value throug applying two scenarios. PMP will obtained using the rainfall data from Global Satellite Mapping of Precipitation (GSMaP) which has temporal resolution 1 hourly. The rainfall data firstly corrected using the bias correction and it showed that the bias correction could change the data distribution approached the observation data. Then, PMP value will obtained with the statistical Hershfield method, and the PMF will obtained by using the PMP value as the input data in Gridded Surface Subsurface Hydrologic Analysis (GSSHA). Spatially, the biggest PMP value was in Cimahi and Soreang where its value reached 100 to 150 mm for 6 to 12 hours duration, Cimahi and Bandung reached around 250 mm for 24 hours duration. GSSHA model simulation with the A scenario get the PMP value from each GSMaP data grid and B scenario get the PMP value from the rainfall area of upper Citarum Watershed. Both PMF hydrographs from both scenarios showed for PMP duration equal or more than 72 hours very saturated condition occured, and it was showed the same response from the watershed which it means weather A or B scenario could used in the upper Citarum watershed for that duration. A scenario generate peak discharge 13,12% larger than B. The similarity and difference affected by PMP intensity and the upper Citarum watershed concentration time.